A novel “holey-LFP / graphene / holey-LFP” sandwich nanostructure with significantly improved rate capability for lithium storage - Lu, Jiming; Tian, Xiaohui; Zhou, Yingke; Zhu, Yanbin; Tang, Zhihao; Ma, Ben; Wu, Guan; Jiang, Tingting; Tu, Xiaofeng; Chen, George Z. (Elsevier Ltd, 2019)
The development of high-performance and new-structure electrode materials is vital for the wide application of rechargeable lithium batteries in electric vehicles. In this work, we design a special composite electrode structure with the macroporous three-dimensional graphene areogel framework supporting mesoporous LiFePO4 nanoplate. It is realized using a simple sol-gel deposition method. The highly conductivity graphene nanosheets assemble into an interconnected three-dimensional macroporous areogel framework, while LiFePO4 grows along the graphene nanosheets and generates a mesoporous nanoplate structure. In comparison with LiFePO4, this unique sandwich nanostructure offers a greatly increased electronic conductivity thanks to the framework of graphene nanosheets. Also, the bimodal porous structure of the composite remarkably increases the interface between the electrode/electrolyte and facilitates the transport of Li+ throughout the electrode, enabling the superior specific capacity, rate characteristic and cyclic retention.